Hypoxia releases S-nitrosocysteine from carotid body glomus cells—relevance to expression of the hypoxic ventilatory response - Seckler, James M.; Getsy, Paulina M.; May, Walter J.; Gaston, Benjamin; Baby, Santhosh M.; Lewis, Tristan H. J.; Bates, James N.; Lewis, Stephen J. (Frontiers in Pharmacology, 2023)
We have provided indirect pharmacological evidence that hypoxic gas challenges may release the S-nitrosothiol, S-nitroso-L-cysteine (L-CSNO) from primary carotid body glomus cells (PGCs) of rats to elicit the hypoxic ventilatory response (HVR) by activation carotid body chemoafferents. The objectives of this study were to provide direct evidence using our capacitive S-nitrosothiol sensor that L-CSNO is stored and released from PGCs extracted from male Sprague-Dawley rat carotid bodies and further pharmacological evidence for their role in mediating the HVR. Key findings were that (1) lysates of PGCs contained an S-nitrosothiol with physicochemical properties similar to L-CSNO rather than S-nitroso-L-glutathione (L-GSNO), (2) exposure of PGCs to a hypoxic challenge caused a significant increase in S-nitrosothiol concentrations in the perfusate to levels approaching 100 fM via a mechanisms that required extracellular Ca 2+ , (3) the dose-dependent increases in minute ventilation elicited by arterial injections of L-CSNO and L-GSNO were likely due to activation of small diameter unmyelinated C-fiber carotid body chemoafferents, (4) L-CSNO but not L-GSNO responses were markedly reduced in rats receiving continuous infusion (10 μmol/kg/min, IV) of both S-methyl-L-cysteine (L-SMC) and S-ethyl-L-cysteine (L-SEC), ( 5) ventilatory responses to hypoxic gas challenge (10% O2, 90% N2) were also due to the activation of small diameter unmyelinated C-fiber carotid body chemoafferents, and (6) the HVR was markedly diminished in rats receiving L-SMC plus L-SEC. This data provides evidence that rat PGCs synthesize an S-nitrosothiol with similar properties to L-CSNO that is released in an extracellular Ca 2+ -dependent manner by hypoxic challenge.